Survive the north: transplantation for conservation of mangrove forests requires consideration of influences of low temperature, mating system and their joint effects on effective size of the reforested populations - Lu, Wen-Xun; Zhang, Bing-Huang; Yang, Sheng-Chang (Frontiers in Ecology and Evolution, 2023)
Mangrove forests, which occur in the intertidal regions of tropical and sub-tropical zones, have high ecological and economic values. They have rapidly reduced over the past decades due to various reasons. Reforestation is a common strategy for the conservation of mangroves, but information on the renewal capacity and viability of these artificial mangrove populations is still lacking. Here, we estimated the effective population size (NE) of an artificial population of Kandelia obovata (Rhizophoraceae) and explored the effects of intrinsic and extrinsic factors on changes in NE to evaluate population viability and develop appropriate management strategies for mangrove forests. This population consisted of three ecologically and genetically differentiated groups that had experienced a major low-temperature event during the winter of 2015–2016 and varied in cold resistance. We first detected population bottlenecks and estimated contemporary values of NE for different groups using microsatellite data. Next, we performed paternity analyses for seedlings and propagules to explore variations in the reproductive success of individuals within the three groups before and after the low-temperature event. Lastly, we simulated four scenarios to characterize the effects of low temperature, mating system, and variance in reproductive success on changes in NE in a hypothetical metapopulation based on empirical estimates. Our results show that groups with moderate or poor cold resistance experienced local bottlenecks, and shifts in effective breeders occurred following the low-temperature event, which indicates that low temperature has an effect on not only population size but also reproductive success. Furthermore, our simulations revealed that changes in NE are jointly affected by reproductive success, mating system, and environmental conditions. These findings enhance our understanding of the multiple factors that affect NE, and provide key information that will aid the reforestation and management of mangrove forests, especially when they are introduced to high-latitude areas.